Technologies and technique: philosophy of technology before and after the empirical turn - Gerola, Alessio (Mechane, 2020)
Contemporary philosophy of technology presents itself as a very diversified field, offering a wide range of different approaches and theories. The aim of this paper is to offer a short thematic introduction to a set of specific trends of inquiry that blossomed following the so-called empirical turn in philosophy of technology in the 1980s. These approaches are characterized by the refusal of certain core assumptions that informed so-called classical philosophy of technology, which framed technology as a monolithic and autonomous force that reorganizes human life according to its own rational logic of efficient production. The first section identifies these theoretical nodes by presenting fundamental aspects of technology as discussed by classical philosophers of technology. The second section elaborates on the critiques to classical assumptions that followed the empirical turn, and the different research programs it generated. The last section delves into a specific approach in more detail, namely, postphenomenology, to offer an illustrative example of the kinds of questions and methodologies that an empirical approach is able to address. In this way this paper provides some indicative guidelines into philosophy of technology to interested scholars, and encourages engagement across different traditions.